PERSONALIZATION IN DIGITAL MARKETING: EXPLORING ITS IMPACT ON CONSUMER TRUST AND LOYALTY - Marasabessy, Nabila Cecilia; Hidayat, Muhammad (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This research aims to explore how personalization in digital marketing influences consumer trust, focusing on factors that strengthen or weaken that trust. Using a systematic literature review approach with the PRISMA method, we analyzed findings from previous studies related to data-based personalization, transparency, and privacy. The results show that the level of transparency, relevance of content, as well as consumer control over their data play a key role in building trust, while intrusive personalization can undermine it. The practical implications of this research provide guidance for companies in designing ethical and effective digital marketing strategies.